PENINGKATAN KEMAMPUAN MEMAHAMI MUFRADAT MATA PELAJARAN BAHASA ARAB MELALUI MODEL MAKE A MATCH SISWA KELAS V MINU NGINGAS WARU SIDOARJO - Musfiroh, Lailatul (Journal Of Islamic Elementary School (JIES), 2017)
This research was conducted based on the problem that it was found that the ability to understand the mufradat of the fifth grade students of MINU Ngingas Waru Sidoarjo was still lacking. Based on the pre-cycle results of 31 students, only 8 students scored above the KKM while 23 others were still below the KKM. This is because the approach used when the learning process is Teacher Center, so that students do not play an active role in the learning process and hinder students’ understanding. Therefore, to improve students’ understanding of mufradat, researchers used the make a match model. The formulations of the problems in this study are: (1) How is the application of the make a match model in order to improve the understanding of mufradat in Arabic in class V MINU Ngingas Waru Sidoarjo ?. (2) How to increase the understanding of mufradat in Arabic after the make a match model is applied in class V MINU Ngingas Waru Sidoarjo ?. This type of research uses a qualitative descriptive approach to classroom action research (CAR) which is carried out in two cycles according to Kurt Lewin’s model. The data collection techniques used were observation, interviews, documentation, written tests and non-tests in the form of products. The data obtained were analyzed using the average value and the percentage of student learning completeness based on a predetermined formula. Based on the results of the study, it shows that: (1) the application of the make a match model goes well, as evidenced by the results of teacher and student observations. The results of observations of teacher activities in the first cycle obtained a percentage of 88% with good criteria. and in the second cycle obtained a percentage of 95% with very good criteria. the results of student observations in the first cycle obtained a percentage of 85% with good criteria. and the results of student observations in cycle II obtained a percentage of 92% with very good criteria. (2) the understanding of mufradat also experienced an increase in pre-cycle activities reaching an average of 61.00 to 68.36 in the first cycle and increasing again to 88.74 in the second cycle. Likewise, the percentage of learning completeness in pre-cycle activities was 26.66% to 60.34% in cycle I and increased again to 91.66% in cycle II.